Analysis of the world's most innovative companies on the basic of industry: 2005-2014 - Erciş, Aysel; Ünalan, Musa (My University, 2015)
In most industries, almost everywhere in the world, growth is harder and harder for companies to generate. Therefore, searching for new sources of growth, companies across all industries and regions are increasing their spending on innovation every year. As a result, innovation continues to be a top corporate priority for the many companies. This paper to aims to emphasize importance of innovation for companies and to analyse the most innovative companies on basic of the industry between 2005 and 2014. The contribution of this paper consists in analysing the world's 50 most innovative companies by listed Boston Consulting group (BCG) in terms of range and industrial distribution. The other aim of this paper is to determine to which companies come from which countries and region in terms of companies listed. Our sample consists in 50 companies listed on BCG each year. The results reflect that companies specializing in digital technologies hold the top places or top ten in recent years. The other companies from different sectors compare in itself between 2005 and 2014.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Innovation; Innovative Companies; Industry; Digital Technologies